Porous nucleating agents for protein crystallization - Khurshid,S; Saridakis,E; Govada,L; Chayen,NE (Nature Protocols, 2014)
Solving the structure of proteins is pivotal to achieving success in rational drug design and in other biotechnological endeavors. The most powerful method for determining the structure of proteins is X-ray crystallography, which relies on the availability of high-quality crystals. However, obtaining such crystals is a major hurdle. Nucleation is the crucial prerequisite step, which requires overcoming an energy barrier. The presence in a protein solution of a nucleant, a solid or a semiliquid substance that facilitates overcoming that barrier allows crystals to grow under ideal conditions, paving the way for the formation of high-quality crystals. The use of nucleants provides a unique means for optimizing the diffraction quality of crystals, as well as for discovering new crystallization conditions. We present a protocol for controlling the nucleation of protein crystals that is applicable to a wide variety of nucleation-inducing substances. Setting up crystallization trials using these nucleating agents takes an additional few seconds compared with conventional setup, and it can accelerate crystallization, which typically takes several days to months.